Optimal deployment of solar PV power plants as fast frequency response source for a frequency secure low inertia power grid - K. Wamukoya, Brian; K. Kaberere, Keren; M. Muriithi, Christopher (Bulletin of Electrical Engineering and Informatics, 2025)
Modern power systems are witnessing increased uptake of solar photovoltaic power plants (SPVPPs) replacing conventional synchronous generators (SGs). SPVPPs lack any rotating parts resulting in no natural rotational inertia contribution to the grid. Reduced inertia makes the power system more dynamic, making it susceptible to frequency instability caused by minor disturbances. This problem is majorly addressed by limiting the penetration of SPVPPs to ensure a minimum level of critical inertia is maintained or by providing additional virtual inertia from an energy storage system. However, the SPVPPs can be configured to operate below maximum power point tracking (MPPT) (deloaded mode) to provide a reserve capacity that can rapidly be deployed as fast frequency response (FFR) in case of a frequency event. This paper presents a strategy to optimize the FFR capacity of a deloaded SPVPP using particle swarm optimization (PSO) algorithm. DIgSILENT PowerFactory was used to model the deloaded SPVPP and run time domain simulations. PSO algorithm was implemented using a Python script in PowerFactory. The proposed strategy was applied on a modified IEEE 39 bus test system. The results show that optimal deloading of SPVPP can help to successfully arrest frequency decline, reduce power curtailment while adhering to the prescribed constraints.